THE SYNCRETISM OF THE BISSU CUSTOMS OF PANGKEP, SOUTH SULAWESI WITH ISLAMIC LAW - Jusalim Sammak; Haeruddin; Muh. Ilham Azis; Ahmad Muhajir (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
This study examines the phenomenon of syncretism between Bissu customs in Pangkep Regency, South Sulawesi, and the principles of Islamic law. Bissu, as customary leaders, have spiritual, social, and cultural functions that have been passed down through generations. Their identity, which straddles both male and female (calabai), and their particular ritual practices often spark debate from an Islamic perspective. They are often marginalized or ostracized by society because they are considered to reject the inherent nature of men, even though they are actually men, but within their bodies, they possess the souls and feelings of women. This study uses a normative-empirical approach based on interviews with traditional, religious, and community leaders, as well as a literature review referring to the Quran, Hadith, and the opinions of Islamic scholars. The results of the analysis show that Bissu customs can be accepted as long as they are within the corridor of monotheism and do not contain polytheistic practices, while rituals with metaphysical spiritual nuances need to be reinterpreted according to maqāṣid al-syarī‘ah in order to maintain public welfare.